The Role of Strategic Human Resource and Project Management in Building Sustainable Business (Jurnal Bisnis dan Manajemen West Science, 2026)
In today's dynamic business environment, successfully completing the project within the constraints of time, cost and scope does not lead to organizational success. Strategic Project Management has emerged as important strategy, linking the strategic objectives of an organization with the strategic project goals and taking into account social, economic and environmental sustainability. Also, Strategic Human Resource Management is significant for developing human capital, increasing the employee commitment and organization long-term sustainability. Based on the relevant theories such as Sustainable Human Resource Management Theory, Social Exchange Theory, Human Resource Theory, and the Resource-Based View (RBV), this study investigates the Strategic Human Resource Management and Strategic Project Management in the Sustainable Business Development. Quantitative approach based on questionnaire survey was adopted and was administered to the people who participated in organizational activities. This study was conducted by descriptive statistic, reliability analysis, correlation analysis, hypothesis testing.
Keywords: Strategic Project Management; Strategic Human Resource Management; Sustainable Business Development; Resource Based View; Sustainable HRM; Employee Commitment; Human Capital Development; Competitive Advantage